Motivations of medical students and doctors leaving the NHS explored in a residency training application webinar series. Issue 1166 (21st October 2021) - Ooi, Setthasorn Zhi Yang; Ooi, Rucira; Godoi, Amanda; Foo, Eu Fang; Woo, Timothy; Li, Chunhei; Ganesananthan, Sashiananthan; ,
Abstract: Background: Recent reports show that about 10% of UK-graduate doctors leave the country to pursue specialty training elsewhere. Our article aims to evaluate the motivating factors for UK graduates to leave the National Health Service (NHS), especially during the COVID-19 pandemic and Brexit. Study design: Cross-sectional study. Method: A novel 22-item questionnaire was disseminated at a webinar series regarding the application process to pursue residency training in six different countries/regions from 2 August 2020 to 13 September 2020. The data was analysed using Kruskal-Wallis rank-sum with post-hoc Wilcoxon test to compare the difference in significance among the motivating factors. Results: 1118 responses from the UK medical students and doctors were collected; of which, 1001 (89.5%) were medical students, and 88 (7.9%) were junior doctors. There was a higher propensity for leaving after the Foundation Programme compared with other periods (p<0.0001 for all comparisons). There was no difference between desire for leaving after core surgical/medical training and specialty training (p=0.549). However, both were significantly higher than leaving the NHS after medical school (p<0.0001). Quality of life and financial prospects (both p<0.0001) were the most agreed reasons to leave the NHS, followed by clinical and academic opportunities and, subsequently, family reasons. Conclusion: Future work on the quality of life for doctors in the UK should be explored, especially among those considering leaving the NHS. Policymakers should focus on assessing the difference in working hours, on-call hours and wages that may differ among healthcare systems.